2007
DOI: 10.1002/ar.20625
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte Loss in Aging OVE26 Diabetic Mice

Abstract: Recent studies show that podocyte nuclear density (N V ) and numbers of renal podocytes per glomerulus (N) are altered in experimental and spontaneous diabetes mellitus. N V and N are generally reduced, and it has been hypothesized that these morphological changes may relate to the loss of glomerular permselectivity in diabetic nephropathy (DN). In the current study, OVE26 transgenic diabetic mice and age-matched (FVB) controls (60, 150, or 450 days) were fixed by vascular perfusion and renal cortical tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 41 publications
7
40
1
1
Order By: Relevance
“…Whereas C57Bl/6J mice are relatively resistant to a variety of kidney disease models, 24 the FVB/N strain of mice used in this study are susceptible to various forms of renal injury. [32][33][34] In this study, attenuation of albuminuria in 5/6 Nx EP4 podϪ/Ϫ mice was incomplete, which may reflect the inefficient nature of the Cre-mediated EP4 gene deletion. Despite that our CreEGFPpodϩ /ROSA26 mice exhibited qualitatively robust glomerular Cre-recombinase activity, we were unable to obtain a reduction in EP4 mRNA beyond 50% in podocytes isolated from EP4 podϪ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 68%
“…Whereas C57Bl/6J mice are relatively resistant to a variety of kidney disease models, 24 the FVB/N strain of mice used in this study are susceptible to various forms of renal injury. [32][33][34] In this study, attenuation of albuminuria in 5/6 Nx EP4 podϪ/Ϫ mice was incomplete, which may reflect the inefficient nature of the Cre-mediated EP4 gene deletion. Despite that our CreEGFPpodϩ /ROSA26 mice exhibited qualitatively robust glomerular Cre-recombinase activity, we were unable to obtain a reduction in EP4 mRNA beyond 50% in podocytes isolated from EP4 podϪ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 68%
“…[23][24][25][26][27] Several studies have indicated that loss of podocytes plays an important role in age-related glomerulosclerosis. 26,[28][29][30] It was unclear until now whether lost podocytes were at least partially regenerated and if age-related glomerulosclerosis was, thus, caused by an insufficient replacement of podocytes. 31 The aged PEC-rtTA mice showed typical changes within the glomerulus associated with kidney aging 27 (i.e., mesangial matrix expansion, thickening of the GBM with formation of spikes/humps, proteinuria, and podocyte hypertrophy).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in podocyte density is an accurate predictor of glomerular disease progression. 27 The reduction in podocyte number led to the podocyte density in Yap-KO mice being significantly lower than that of control littermates (436 6.4 versus 3061.5310…”
Section: Yap Deletion Causes Podocyte Depletionmentioning
confidence: 99%